2020
DOI: 10.1111/odi.13524
|View full text |Cite
|
Sign up to set email alerts
|

TMJ arthroscopy with hyaluronic acid: A 12‐month randomized clinical trial

Abstract: Objectives To determine the effects of hyaluronic acid (HA) as an adjunct to temporomandibular joint (TMJ) arthroscopy, relative to standard TMJ arthroscopy, in Wilkes stage‐III and stage‐IV patients. Methods A randomized clinical trial design was utilized (ClinicalTrials.gov NCT04110587). 51 patients were allocated to a TMJ arthroscopy (n = 25) or a TMJ arthroscopy plus HA (n = 26) group. Visual analog scale joint pain scores, maximum mouth opening (MMO), and muscle pain were measured at baseline, and at 3, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…No differences were observed between the two groups in VAS pain score, maximum mouth opening, and disk position by MRI at months 3, 6, 9, and 12. 23 …”
Section: Resultsmentioning
confidence: 99%
“…No differences were observed between the two groups in VAS pain score, maximum mouth opening, and disk position by MRI at months 3, 6, 9, and 12. 23 …”
Section: Resultsmentioning
confidence: 99%
“…Hyaluronic acid was injected during the arthroscopic procedure in four joints where there were signs of severe degenerative joint disease as it might have a positive effect on pain reduction [26]. However, a recent randomized controlled trial published in 2021 with 51 patients (Wilkes stage-III and stage-IV) observed no beneficial effect of hyaluronic acid on pain reduction compared to arthroscopy alone [27]. These new insights were not available at the time the arthroscopies were performed but are important to take into account when performing arthroscopies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of arthroscopy was correlated to that of arthroscopy followed by an injection of plasma rich in growth factors (PRGF) in a total of four articles, where all of them were of low or medium risk of bias. 35,36,67,71 However, Castano-Joaqui et al had not included the post-operative values of MIO or TMJ pain and were therefore not included. 67 Leketas et al were only presenting the MIO mean value at 1-week post-operative and were therefore disregarded in the MIO analysis.…”
Section: Arthroscopy Versus Arthroscopy and Prgfmentioning
confidence: 99%
“…35,36,67,71 However, Castano-Joaqui et al had not included the post-operative values of MIO or TMJ pain and were therefore not included. 67 Leketas et al were only presenting the MIO mean value at 1-week post-operative and were therefore disregarded in the MIO analysis. 71 Neither MIO, nor TMJ pain differed between the two treatment groups in a significant way (MIO: MD 0.95, 95% CI −0.36 to 2.25; TMJ pain: MD −0.39, 95% CI −0.95 to 0.17)…”
Section: Arthroscopy Versus Arthroscopy and Prgfmentioning
confidence: 99%
See 1 more Smart Citation